2020
DOI: 10.3390/microorganisms8040552
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Multispectral Imaging (MSI) for Microbiological Quality Assessment of Poultry Products

Abstract: The aim of this study was to investigate on an industrial scale the potential of multispectral imaging (MSI) in the assessment of the quality of different poultry products. Therefore, samples of chicken breast fillets, thigh fillets, marinated souvlaki and burger were subjected to MSI analysis during production together with microbiological analysis for the enumeration of Total Viable Counts (TVC) and Pseudomonas spp. Partial Least Squares Regression (PLS-R) models were developed based on the spectral data acq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 64 publications
2
15
0
Order By: Relevance
“…Microbial enumeration revealed that TVC of chicken breast and thigh fillets were found at relatively low levels and within the bacterial loads usually reported in the literature for chicken and other poultry meats [ 7 , 51 , 52 , 53 , 54 , 55 ]. Briefly, the initial microbial biota of both chicken parts consisted mainly of Pseudomonas , Br.…”
Section: Discussionsupporting
confidence: 73%
“…Microbial enumeration revealed that TVC of chicken breast and thigh fillets were found at relatively low levels and within the bacterial loads usually reported in the literature for chicken and other poultry meats [ 7 , 51 , 52 , 53 , 54 , 55 ]. Briefly, the initial microbial biota of both chicken parts consisted mainly of Pseudomonas , Br.…”
Section: Discussionsupporting
confidence: 73%
“…Moreover, MSI results on intra-batch performance and its low RMSE suggested that this analysis could be applicable for internal validation or quality control in the production line. The latter option has been confirmed via experiments performed in the production line of chicken products at industrial level ( Spyrelli et al., 2020 ). Furthermore, the fundamental role of training and testing data set definition is demonstrated by FT-IR lars model during B1 on B2 validation, which significantly outperformed batch-on-batch performance of MSI (RMSE: 0.851 vs 1.251 log CFU/cm 2 ).…”
Section: Discussionmentioning
confidence: 79%
“…The wavelengths 630, 645, 660, 700, and 850 nm were identified as significant (b coefficient greater than 0.2) for determining TVCs counts on the surface of chicken thigh. The significant contribution of the wavelength range 630-700 nm for the determination of meat and poultry spoilage has been reported in previous studies, and could be linked to myoglobin, metmyoglobin, deoxymyoglobin or oxymyoglobin [11,20]. According to the B regression coefficients of the PLS-R models, the quantitative equations for the estimation of TVCs and Pseudomonas spp.…”
Section: Correlation Of Microbiological Data To Spectral Informationmentioning
confidence: 74%
“…Moreover, fecal contaminants in poultry line [18] and the presence of tumors on the surface of chicken breasts [19] have been accurately detected via MSI analysis. This innovative method was successfully employed in the at-line estimation of the time from slaughter in four different poultry products [20].…”
Section: Introductionmentioning
confidence: 99%